Influência do tratamento com ácido lipoico sobre o metabolismo ósseo e perfil antioxidante de mulheres na perimenopausa - Freire Neto, Francisco Paulo (2010)
Bone is a dynamic tissue that is in constant process of remodeling in response to mechanical stress and hormonal changes. This study aimed to understand the relationship between the biochemical changes, which women in the menopausal transition are subject to, and how the use of an alternative therapy with lipoic acid (LA) could influence these changes. The study of double-blind, was carried out in perimenopausal women that underwent a three month treatment with 600 mg of AL compared with another group that received placebo during the same period. This study showed that women had a waist circunference and body mass index above the values recommended by WHO (WC ≥ 80 cm; BMI > 25kg/m2). Associated with this, these women had increased concentrations of total cholesterol and triglycerides, and borderline LDL (Total Cholesterol > 200mg/dL; Triglycerides > 150mg/dL; LDL >130mg/dL). These changes were not affected by treatment with AL. There were no shifts in liver profile (ALT, AST and GGT), kidney profile (urea, creatinine, total protein and albumin), mineral profile (Total Calcium, Ionized Calcium, Phosphorus and Magnesium) as well in bone markers (osteocalcin, Total Alkaline Phosphatase and Tartrate Resistant Acid Phosphatase) after treatment with LA. The results of the oxidative profile showed that treatment with LA decreased GPx activity (p < 0,01), while for the TBARS, GSH and SOD activity there were no differences. With regard to SOD, this enzyme will submit to be high in the placebo group after 3 months of study (p<0,05). The expression of RANKL mRNA was reduced (p < 0,05) and of RANK increased (p <0.001), after treatment with LA, while the expression of IL-6 and TNF-ɑ genes were no changed. We conclude that women already in the perimenopause stage have changes in lipid profile and body composition that could induce shifts in oxidative and bone metabolism. However, LA treatment has provided an effective effect in the oxidative and bone profile since the earliest markers such as GPx activity and mRNA expression of RANKL, respectively, were reduced associated with no change in SOD activity. These results suggest a beneficial and protective effect of LA, indicating it potential as an alternative treatment to help the to prevent the complications associated with estrogen deficiency